Interpersonal communication between lecturers with students in Wira Bhakti Denpasar College - Merta, I Nengah (International research journal of management, IT and social sciences, 2019)
This study examines "Interpersonal Communication between Lecturers and Students at Wira Bhakti Denpasar College". Interpersonal Communication Ability is a skill that must be carried by individuals in interacting with individuals in interacting with other individuals or groups of individuals. Interpersonal ability is what someone uses when communicating and dealing with other people face to face. Social Communication implies that communication is important to build self-concept, for survival, self-actualization, to gain happiness, to avoid pressure and dependence, among others, through entertaining communication and fostering relationships. Through social communication can work together with community members (family, study groups, colleges, village, city, and the country as a whole) to achieve common goals. The problem in this study is, How do leaders implement interpersonal communication which includes; openness, supportive behavior, positive behavior (positiveness), empathy (empathy) and equality at Wira Bhakti Denpasar College. The purpose of this study was to find out and describe the interpersonal communication of lecturers with students in an effort to build and improve performance at Wira Bhakti Denpasar College.